Gambaran Pemberian Olive Oil pada Ibu Hamil Trimester III dengan Striae Gravidarum - Safira Salsabila Nugraha; Enny Yuliaswati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Pregnant women in the third trimester experience anxiety due to stretch marks, striae gravidarum, and heartburn. This research aims to determine the description of giving olive oil to pregnant women in the third trimester with striae gravidarum in the working area of Mulya Asri Health Center, West Tulang Bawang Regency in 2023. This type of research is qualitative descriptive with observational methods. The samples used in this research were 18 pregnant women in the third trimester at the Mulya Asri Community Health Center, Tulang Bawang Barat, with samples taken using the Purposive Sampling Technique. Data analysis techniques use statistical analysis and percentage formulas. The results of the study showed that the highest age of pregnant women was 21-34 years old, with 17 pregnant women (94.44%). Meanwhile, age > 35 years was 1 respondent (5.56%). striae gravidarum with multigravida status were 11 respondents (61.11%). Meanwhile, there were 7 respondents who experienced striae gravidarum with primigravida status (38.89). At the high school level the number of respondents was 10 (55.56%) and the least was at the D3 level, 1 respondent (5.56%). In this way, health services are expected to provide information for optimal knowledge of pregnant women.